Analisis Faktor-Faktor yang Mempengaruhi Kualitas Kesejahteraan Hidup di Jawa Timur Tahun 2023 Menggunakan Metode Analisis Faktor - Ammaar Razaan Yahya; Virda Wulandari; Sri Pingit Wulandari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The quality of welfare is an important indicator in assessing the social and economic development of a region, including in East Java, which has the second largest population in Indonesia. This study aims to analyze the factors that influence the quality of welfare in East Java in 2023, focusing on variables such as average food and non-food expenditure, the number of poor people, average years of schooling, life expectancy, and open unemployment rate. Data from the Central Bureau of Statistics shows that the percentage of poor people reached 10.35% and the open unemployment rate was 4.33%. The factor analysis method was used to identify the relationship between these variables and ensure the assumption of multivariate normality before the analysis was conducted. The results of the data characteristics analysis showed that all quality of life factors had asymmetrical distributions, with medians that were not centered, and outliers in the food and non-food expenditure data. Testing the assumptions of factor analysis indicated that the data met the requirements of multivariate normal distribution, dependence, and adequacy for further analysis. From the factor analysis, two new significant components were found, namely social and economic education and population and education. These findings provide important insights into the main dimensions affecting people's welfare in East Java, which can form the basis for the development of more effective socioeconomic policies.